Minat Peserta Didik Kelas V pada Pembelajaran TIK di SD Muhammadiyah Pakel - Lovandri Dwanda Putra; Sabila Hanifatun Fatihah; Armila Wulandari; Sherly Rachmadhani (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
The field of education is affected by the development of Information and Communication Technology. Causing the emergence of ICT lessons. The purpose of this research is to find out the phenomena that occur in students' interest in learning ICT in fifth grade students of the Amanah class at SD Muhammadiyah Pakel Yogyakarta as many as 31 students. Contains 17 males and 14 females. Collect information by distributing questionnaires to students' interest in learning subjects. The results of this study show that the average interest in ICT lessons at Muhammadiyah Pakel Elementary School is 75.39% with the indicator that students are interested in ICT subjects.